'No Smoke without Fire': Citizenship and Securing Economic Enclaves in Mozambique. Issue 6 (25th April 2019) - Buur, Lars; Sumich, Jason
ABSTRACT: This article explores the complicated interrelationship between economic enclaves, their associated security practices and the formation of national citizens in Mozambique. From the colonial era of company rule to the large‐scale foreign direct investments of the present day, investors have feared the destructive fires of rampant 'mobs', unruly workers and the potentially rebellious populace more generally. Signs of smoke point to trouble for investors, who can draw on complex security arrangements, including corporate social responsibility programmes, unions, private security companies, community leaders, state police and specialized state and rapid response units with the latest communications and transport technologies, to try to protect their investments from labour unrest and political demands. Through a variety of ethnographic materials on mega‐investments in the sugar industry over the last two decades, the article explores the centrality of complex security arrangements to strategies of governance that use such arrangements in an attempt to produce disciplined national subjects.